Clinical high risk for psychosis: gender differences in symptoms and social functioning - Rietschel, Liz; Zink, Mathias (Early intervention in psychiatry, 2017)
Aim: Schizophrenia is a heterogeneous disorder that presents differently in men and women: men show a higher propensity to negative symptoms, lower social functioning, earlier age at onset and co-morbid substance abuse, whereas women display more affective symptoms. It is unknown whether these differences extend to subjects at high risk (HR) of psychosis. Thus, the aim of the present study was to address this question. Methods: Clinical symptoms and functioning were assessed using structured interviews in 239 HR subjects (female, n = 80). The definition of being at HR was based on the criteria used in the European Prediction of Psychosis Study (EPOS). Results: Men displayed more pronounced negative symptoms, higher rates of past substance abuse disorders and higher deficits in social functioning. No gender difference was found for depression, which affected almost 50% of the cohort, or age at onset for the fulfilment of HR criteria. Conclusion: The higher impairment in specific symptoms observed in male schizophrenia patients was also present in subjects at HR for psychosis. Further studies are required to determine whether these symptoms are gender-specific predictors of transition to psychosis and whether they warrant gender-specific interventions. The high propensity to depression in the present cohort, which was particularly pronounced in the male cohort compared with the general population, in conjunction with the observed increase in negative symptoms and functional impairment, should alert clinicians to the necessity for the identification and treatment of HR subjects, irrespective of the degree to which these features are associated with transition risk.
First published: 24 March 2015
Gesehen am 12.07.2018
First published: 24 March 2015